1996
DOI: 10.1002/(sici)1098-2264(199612)17:4<225::aid-gcc4>3.3.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Three distinct commonly deleted regions of chromosome arm 16q in human primary and metastatic prostate cancers

Abstract: Human prostate cancers frequently show loss of heterozygosity (LOH) at loci on the long arm of chromosome 16 (16q). In this study, we analyzed prostate cancer specimens from 48 patients (Stage B, 20 cases; Stage C, 10 cases; cancer death, 18 cases) for allelic loss on 16q, using either restriction fragment length polymorphism (RFLP)- or polymerase chain reaction (PCR)-based methods. Allelic losses were observed in 20 (42%) of 48 cases, all of which were informative with at least one locus. Detailed deletion ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…Chromosome 16q is another region commonly affected in prostate cancer; the candidate TSG E‐cadherin is located on 16q22.1 [25]. Two candidates for TSGs, DCC and DPC4 (also termed Smad4 ) have been reported on the long arm of chromosome 18 [26].…”
Section: Discussionmentioning
confidence: 99%
“…Chromosome 16q is another region commonly affected in prostate cancer; the candidate TSG E‐cadherin is located on 16q22.1 [25]. Two candidates for TSGs, DCC and DPC4 (also termed Smad4 ) have been reported on the long arm of chromosome 18 [26].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of function in E-cadherin and/or other collaborating proteins contributes to increased proliferation, invasion and metastasis in many malignant epithelial tumours [22,23]. Mutations in E-cadherin , which encodes a transmembrane protein, have been described in cancers of the endometrium and ovary [11], signet ring cell carcinoma of the stomach [24,25], the diffuse sclerosing variant of papillary thyroid carcinoma [26], invasive lobular breast cancer [5,19,27,28], and diffuse and mixed gastric cancer [24,28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Loss of heterozygosity (LOH) studies in breast and prostate cancer have identified chromosome region 16q24.3 as the probable position of a tumour suppressor gene (Suzuki et al 1996;Brenner and Aldaz 1997). We have previously described a detailed physical and transcription map encompassing a region of approximately 940 kb within this 16q24.3 LOH region, from which a number of known genes and potential transcripts have been localized (Whitmore et al 1998).…”
Section: Introductionmentioning
confidence: 99%